2020
DOI: 10.18549/pharmpract.2020.1.1804
|View full text |Cite
|
Sign up to set email alerts
|

How many manuscripts should I peer review per year?

Abstract: Peer review provides the foundation for the scholarly publishing system. The conventional peer review system consists of using authors of articles as reviewers for other colleagues' manuscripts in a collaborative-basis system. However, authors complain about a theoretical overwhelming number of invitations to peer review. It seems that authors feel that they are invited to review many more manuscripts than they should when taking into account their participation in the scholarly publishing system. The high num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…For instance, the median review time has grown from 85 to 150 days at Nature and from 37 to 125 days for PLoS ONE. 30 31 We found a negligible decrease in publication lag time, which may result from an increasing time devoted to peer reviews 32 being offset by a decreasing online publication time due to the use of early-view and ahead-of-print systems. 33 34 …”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…For instance, the median review time has grown from 85 to 150 days at Nature and from 37 to 125 days for PLoS ONE. 30 31 We found a negligible decrease in publication lag time, which may result from an increasing time devoted to peer reviews 32 being offset by a decreasing online publication time due to the use of early-view and ahead-of-print systems. 33 34 …”
Section: Discussionmentioning
confidence: 75%
“…36 37 Thus, to maximise the novelty of a review, an update of the search is recommended before submission for publication. 32 This can be performed by rerunning searches for all relevant databases days or weeks before submission. If we consider research topics with high publication rates, search strategies should be updated regularly to allow authors to keep track of newly added studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the "climbing upwards" number of existing journals has been blamed for increasing the number of review invitations [45], a recently published mathematical model demonstrated that the total number of reviewers required to publish one paper is inversely related to the acceptance rate, which should increase in parallel to the number of journals. This inverse relationship means that the higher the number of indexed journals, the lower the rejection rate and subsequently the lower the total number of reviewers necessary to publish a given number of articles [46].…”
Section: Plos Onementioning
confidence: 99%
“…Pharmacy Practice published a guide to help determine if a potential article is relevant for an international audience. 11 So, why are researchers compelled to publish what they probably know is an irrelevant article? Again, the scholarly publishing system has been corrupted and converted into a performance-assessment system.…”
mentioning
confidence: 99%